2018
DOI: 10.3889/oamjms.2018.043
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide with a New Pulse Profile and Shape: A Perfect Tool to Perform Labiaplasty for Functional and Cosmetic Purpose

Abstract: OBJECTIVE:To describe the benefits and safety of using Carbon Dioxide Laser in multi-pulse modalities when performing labiaplasty and anatomical variants approach for functional and cosmetic indications.DESIGN:This is a prospective, descriptive case series study.SETTING:Private Practice Quirofano Calculaser Megacentro Pinares Pereira Colombia.POPULATION:One Hundred and twelve women seeking labia minora labiaplasty for functional and cosmetic reasons were enrolled in the study protocol from June 2013 to June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…More recently, in a study involving 112 women aged 15‐62 years old using CO 2 LASER, improvement in overall satisfaction and comfort during intercourse were reported. The rate of complications and the duration of follow‐up were not mentioned …”
Section: Other Possible Uses Of Laser (Vulvar Bleaching/whitening/brimentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in a study involving 112 women aged 15‐62 years old using CO 2 LASER, improvement in overall satisfaction and comfort during intercourse were reported. The rate of complications and the duration of follow‐up were not mentioned …”
Section: Other Possible Uses Of Laser (Vulvar Bleaching/whitening/brimentioning
confidence: 99%
“…The rate of complications and the duration of follow-up were not mentioned. 133 None of the studies have included a control group. In at least two of the studies children were enrolled.…”
Section: Lichen Sclerosusmentioning
confidence: 99%
“…While 25.4% of the study group considered that FGCPs were only a temporary trend, 32.6% thought the opposite. Some authors suggested that labiaplasty and vaginal tightening could improve sexual function and quality of life, whereas others failed to demonstrate improvement ( 19 , 20 , 21 , 22 ) . In January 2020, the ACOG stated in their revised bulletin regarding FGCPs that surgical alteration of the labia that was not necessary to the health of patients aged younger than 18 years was a violation of federal criminal law in the United States ( 9 , 23 ) .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a study involving 112 women aged 15-62 years old using CO 2 LASER, improvement in overall satisfaction and comfort during intercourse were reported. The rate of complications and the duration of follow-up were not mentioned 132 .…”
Section: Labiaplasty)mentioning
confidence: 99%